An Evaluation of the Precision of Ocular Trauma Score and Factors for Poor Visual Outcomes in Open Globe Injury: A Retrospective Analysis of Resourcelimited Hospital Settings - Takarn Oughtkaew; Siwatus Puangrab (Siriraj Medical Journal)
Objective: To evaluate the accuracy and validity of ocular trauma scores (OTS) among patients with open globe injury (OGI) in rural hospital settings and to identify the determinants predicting poor visual outcomes.